PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Almadiah Almadiah; Syahlan Syahlan; Dhia Octariani (MES: Journal of Mathematics Education and Science, 2022)
This study aims to describe the development of the student worksheets based on valid, practical and effective realistic mathematics learning models, and to determine the improvement of students’ critical thinking skills by using student worksheets based on realistic mathematics learning models. The type of research used is Research and Development research which refers to the 4-D model as stated by Thiagarajan (1974). However, in in its implementation, this research is limited to the define, design, and develop stages. The subjects in this study were students of class X IPS-1 SMA Setia Budi Abadi Perbaungan which consisted of 31 students. This research was conducted in the odd semester of 2021/2022 academic year. The research instrument used include the student worksheet assessment sheets to measure the validity, the critical thinking skills test, and student response questionnaires.Based on the results of the trials carried out, it was concluded that the developed student worksheets have fulfilled the validity criteria with an average score of 3.93%. The developed student worksheets have fulfilled the parcticality criteria in terms of the results of the validator’s assessment and student’s responses. The developed student worksheet have fulfiiled the criteria for the effectiveness in terms of. Completeness of learning, student responses, and the use of time in the learning process. The trial was carried out in two stages where there was an increase in the percentage of learning completeness from 35.48% to 93.54% with achievement indicators from 64.77% to 79.97%; student’s responses to learning are included in the effective category with an average of 88.17%; the use of time for the learning process in accordance with the available time allocation. Thus, the developed student worksheets fulfill the valid, practical and effective criteria.